Simulasi Gaya dan Konsumsi Tanda: Fomo dan Trend â€œDresswellâ€ di Tiktok dalam Perspektif Semiotika Baudrillard - Tarisa Dwi Putri; Arief Sudrajat (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the phenomenon of style simulation and sign consumption in the â€œDress Wellâ€ trend on the TikTok platform, which is influenced by Fear of Missing Out (FoMO) in Jean Baudrillard's semiotic perspective. TikTok, as a digital visual medium, not only functions as an entertainment space but also as an arena for the production and reproduction of social signs that shape identity, prestige, and lifestyle standards. The â€œDress Wellâ€ trend is represented through neat, aesthetic, and ideal fashion visuals, which are then constructed as symbols of social status. This study employs a qualitative approach, utilizing semiotic analysis methods to interpret the meaning of signs in TikTok video content, including visual elements, narratives, hashtags, and digital interactions such as likes and comments. The results show that FoMO acts as the primary driver compelling users to follow trends not based on functional needs, but rather for social recognition and digital identity legitimacy. Fashion consumption in the â€œDress Wellâ€ trend is no longer oriented towards utility value, but towards sign value that creates simulation and hyperreality. TikTok content shapes a pseudo-reality that appears more real than everyday life, thereby normalizing symbolic consumption patterns. Thus, the â€œDress Wellâ€ trend represents a practice of digital consumerism that reflects the logic of simulation and hyperreality in contemporary visual culture.